TERAPI KOMPLEMENTER UNTUK MENGURANGI NYERI DADA DAN KECEMASAN PADA PENYAKIT JANTUNG KORONER - Suparda, Dadik Dwi Fata; Ninuk Dian Kurniawati; Andri Setiya Wahyudi (Jurnal Kesehatan, 2024)
Introduction: Coronary heart disease is a health problem that can attack the physical and psychological condition of the patient. Chest pain and anxiety are complaints that are often felt by patients with coronary heart disease. This study aims to review various complementary therapies that can be used to reduce complaints of chest pain and anxiety of coronary heart disease. Methods: a literature review was conducted through four databases (Science direct, Pubmed, ProQuest and Google Scholar) in english languange and limited published in the last five years. The keywords used are complementary, anxiety, chest pain, coronary heart disease, ischemia using boolean AND and OR. This Review analysis using the prisma guideline. Results: The results of the study obtained 15 articles of complementary therapy to reduce complaints of chest pain and anxiety of coronary heart disease patients. Conclusion: Complementary therapies to reduce chest pain complaints in patients with coronary heart disease are left sole massage, foot reflexology, Benson relaxation, and dhikr therapy. Complementary therapies to reduce anxiety in patients with coronary heart disease are using aromatherapy, instrumental music, holly Quran, acupressure, hand reflexology, foot reflexology, Benson relaxation, prayer therapy, and dhikr.